ALK testing methods: is there a winner or loser?. Issue 3 (4th March 2019) - Kozuma, Yuka; Toyokawa, Gouji; Seto, Takashi
ABSTRACT: Introduction : Anaplastic lymphoma kinase (ALK) is one of the most attractive molecular targets for the treatment of patients with non-small-cell lung cancer. Treatment with ALK inhibitors is recognized as the standard-of-care for patients with ALK gene rearrangements, but it is important to appropriately select patients who will benefit from such treatment. Areas covered : In this article, we review the evidence regarding ALK testing. Immunohistochemistry (IHC), fluorescence in situ hybridization (FISH), and reverse transcription polymerase chain reaction (RT-PCR) are the representative methods for detecting ALK gene fusions. Among these diagnostic modalities, IHC in particular exhibits high sensitivity and specificity for the detection of ALK fusions when appropriately applied and interpreted. Expert commentary : Discrepancies have been reported between the results of IHC and FISH. However, it was revealed that patients with IHC-positivity and FISH-negativity may respond to alectinib, indicating that IHC can be used as a stand-alone method from a clinical standpoint for the identification of patients eligible for treatment with ALK inhibitors. In addition, differences between ALK variants have been reported to affect the prognosis and efficacy of ALK inhibitor-based treatments, and RT-PCR will likely increase in importance as a complementary tool.